RESEARCH ON THE SIGNIFICANCE OF READING COMPREHENSION TASKS IN MASTERING RUSSIAN LANGUAGE LESSONS IN HIGHER EDUCATION - Umirova Komila, (International Journal of Innovations in Engineering Research and Technology, 2024)
Reading comprehension in an article is the ability to understand the meaning of the text being read, the ability to interpret it and form an attitude to what has been read. That this is the most important skill that students are taught in elementary school, literal understanding. The first level of comprehension is the repetition or re-creation of the text, highlighting basic information, identifying the main characters, etc. It is said to have the ability to identify the month, place, time, chronology, plot, movement.